Influence of mechanical properties of concrete on the failure behaviour of FRP-to-concrete interface. (20th December 2020) - An, Feng-Chen; Zhang, Fei-Yang; Hou, Chuan-Chuan
Highlights: Failure behaviours of FRP-to-concrete interface are investigated for different failure modes. The failure modes of the specimens include debonding (DBC) and concrete prism failure (CPF) modes. Ultimate load with DBC mode is mainly governed by the compressive fracture energy of concrete. Ultimate load with CPF mode is mainly governed by the tensile fracture energy of concrete. Abstract: This paper presents a numerical study on the influence of mechanical properties of concrete on the failure behaviour of FRP-to-concrete interface. A verified predictive finite element (FE) model is employed to carry out a parametric study on the influence of compressive strength and compressive fracture energy, and tensile strength and tensile fracture energy. Results show that for different failure modes of the FRP-to-concrete interface, their ultimate strengths are determined by different properties of concrete. For the debonding failure in concrete (DBC) mode, the ultimate strength is mainly determined by the compressive fracture energy, while the tensile fracture energy has a moderate influence. For the concrete prism failure (CPF) mode, the ultimate strength is mainly determined by the tensile fracture energy, while the compressive fracture energy has very little effect. Lastly, the failure mechanisms are analysed for the two failure modes.